2018
DOI: 10.1186/s41935-018-0049-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation studies on gender determination from fingerprints with special emphasis on ridge characteristics

Abstract: Background: The present work investigates the ridge characteristics and ridge density of fingerprints to determine gender differences among population of Punjab. The main characteristics studied were general pattern type, ridge density and minutiae or ridge characteristics with respect to general pattern type. Further, instead of using conventional method of ridge counting, Adobe Photoshop cs5 is used to conclude ridge density and minutiae characteristics. Experimental results shows, along with ridge density, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
(14 reference statements)
1
12
0
Order By: Relevance
“…In this study, fingerprint ridge density of females in a given area was significantly higher than their male counterparts at all three counting regions of both hands as is evident from Mann Whitney U test. Our findings correlated with the results of various national and international studies on different populations (Gungadin 2007;Nayak et al 2010;Nithin et al 2011;Gutierrez-Redomero et al 2013;Kumar et al 2013;Rivalderia et al 2015;Thakar et al 2018;Kaur & Kaur 2019). A study of Ceyhan and Sagiroglu (2017) also determined sex using ridge density in the upper right corner of fingertips in the Turkish population.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, fingerprint ridge density of females in a given area was significantly higher than their male counterparts at all three counting regions of both hands as is evident from Mann Whitney U test. Our findings correlated with the results of various national and international studies on different populations (Gungadin 2007;Nayak et al 2010;Nithin et al 2011;Gutierrez-Redomero et al 2013;Kumar et al 2013;Rivalderia et al 2015;Thakar et al 2018;Kaur & Kaur 2019). A study of Ceyhan and Sagiroglu (2017) also determined sex using ridge density in the upper right corner of fingertips in the Turkish population.…”
Section: Discussionsupporting
confidence: 90%
“…A study by Acree (1999) identified for the first time the sex of individuals in Caucasian and African American populations from fingerprint ridge density, which was ascertained by diagonally counting numbers of ridges within a defined area in radial region of distal phalanges of fingertip. Thereafter, numerous cross-sectional studies were performed to explain the variability in fingerprint ridge density with respect to sex (Agnihotri et al 2012;Ahmed and Osman 2016;Thakar et al 2018;Kaur and Kaur 2019) and topological area (Gutierrez-Redomero et al 2008;Nanakorn and Kutanan 2012;Soanboon et al 2016;Wahdan and Khalifa 2017;Kaur and Kaur 2019) which is crucial from anthropological, and forensic fields of study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender determination based on general pattern or ridge density is not new, although the power of these inferences is rather limited when dealing with partial, smudged marks recovered from crime scenes. The frequencies of minutiae have been added to the set of predictors recently [ 24 ]. Differences in number of minutiae and type have been reported in the past as well.…”
Section: Friction Ridge Skin and Its Individualization Processmentioning
confidence: 99%
“…Thereafter, a plethora of studies [4][5][6][7][8][9][10] have established the sex differences with respect to fingerprint ridge density in different populations, but till date very limited work has been carried out to highlight this aspect on convicted criminals. In a recent study, while analysing an association and individualization of dermal digital ridge density of a male penal population Kaur and Sharma 11 demonstrated that prisoner male have ridge density less than 12 ridges and higher than 15 ridges.…”
Section: Introductionmentioning
confidence: 99%